2017
DOI: 10.1016/j.aorn.2017.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Time Out: An Improved Communication Process

Abstract: An enhanced time out is an improved communication process initiated to prevent such surgical errors as wrong-site, wrong-procedure, or wrong-patient surgery. The enhanced time out at my facility mandates participation from all members of the surgical team and requires designated members to respond to specified time out elements on the surgical safety checklist. The enhanced time out incorporated at my facility expands upon the safety measures from the World Health Organization's surgical safety checklist and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Using short breaks to collect one’s thoughts at or before the various critical elements in the procedure provided an opportunity for safer patient care. It was recently reported that a new approach to time‐outs can contribute to more effective communication and, hence, improved patient safety 26. As reported in 2010, the World Health Organization’s recommended surgical time‐out before surgery was an opportunity to identify and resolve potential problems 27.…”
Section: Discussionmentioning
confidence: 99%
“…Using short breaks to collect one’s thoughts at or before the various critical elements in the procedure provided an opportunity for safer patient care. It was recently reported that a new approach to time‐outs can contribute to more effective communication and, hence, improved patient safety 26. As reported in 2010, the World Health Organization’s recommended surgical time‐out before surgery was an opportunity to identify and resolve potential problems 27.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent errors are related to surgical procedures, the location of surgery, laterality, or patient errors [ 6 , 7 , 8 ]. The etiology of the errors is diverse, but the most important ones are: not following the safety guidelines, communication problems within the multidisciplinary team, and a lack of leadership [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to remember that the incidence of adverse events is particularly relevant in the context of surgery, due to the complexity of—and risks associated with—the perioperative process (Collins et al., 2014; Van Delft et al., 2018). However, although inadequate safety procedures in surgical care may result in severe or irreparable harm, or even death, research suggests that 48% of all surgical complications are preventable (Haynes et al., 2009; Nelson, 2017; Van Delft et al., 2018; World Health Organization, 2009b). Furthermore, the number of adverse events reported is low in comparison with the number of surgical procedures that are carried out (Thiels et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to The Joint Commission (2017), there were 1,215 reported sentinel events in the USA between 2004 and 2015. The most widely reported events are errors related to unintended retention of a foreign body, procedure, surgical site, or patient identity (McDowell & McComb, 2016; Nelson, 2017; Twigg & Attree, 2014).…”
Section: Introductionmentioning
confidence: 99%